Nucleic acid-binding specificities of tobacco chloroplast ribonucleoproteins. - Li, Y Q (1991)
Many ribonucleoproteins (RNPs) are involved in the regulation of gene expression at the post-transcriptional level. We previously isolated three nuclear-encoded RNPs from tobacco chloroplasts. Here we report their binding specificities for various nucleic acids. The three RNPs synthesized in vitro were subjected to binding assays using ssDNA, dsDNA and four ribonucleotide homopolymers. The affinities for ribonucleotide homopolymers are higher than those for ssDNA and dsDNA, suggesting that they bind preferentially to RNA in vivo. All three RNPs show high specificities for poly(G) and poly(U) in the presence of 1.2-1.8 M NaCl, providing additional evidence for the similarity to HeLa hnRNP proteins. Possible involvement of these RNPs in the post-transcriptional regulation of chloroplast gene expression is discussed.